Syncretism in Rasolan Tradition among Nahdlatul Ulama Madurese Society - Ellisa M Sholeh (Journal of Nahdlatul Ulama Studies, 2021)
Madura has a variety of cultures, traditions and customs not widely known by the younger generation. Culture and traditions believed hereditary and constitute the identity of the nation must be maintained and conversed by the nation's successor. One of them is Rasolan tradition in Sumber Jerangoh hill, Mandala Village, Rubaru District, Sumenep Regency, Madura Island. Until now, this tradition is still being carried out as a form of gratitude to the one God and Islamic brotherhood because this tradition has made harmony in the life of social structure, especially in Mandala Village. The society of Mandala Village remains enthusiastic in carrying out the Rasolan procession amid the influence of modern culture which has begun to change the mindset of the society of Mandala Village towards culture. Cultures and traditions need to be published widely to society in various ways to conserve regional culture. The Rasolan tradition carried out by the society of Mandala Village, Rubaru district, Sumenep Regency, Madura Island is an annual tradition as a legacy from ancestors. The Rasolan tradition carried out on the hill named "Sumber Jerangoh". Sumber Jerangoh hill is the place where Bhuju' (read: predecessor) societies Burneh Village are, namely Bhuju' Senam and Bhuju' Seloman. Until now, this place is a place which is considered sacred and highly respected by local society. Apart from the tradition of Rasolan as legacy from ancestors that must be carried out, the Burneh society also carries out a ceremony or ritual in the form of Rasolan on the hill of Sumber Jerangoh as a means to remember the services their Bhegatoah/ predecessors who have sacrificed a lot for the development of Burneh village. Therefore, it is considered important that society always pray for and carry out rituals in the implementation of the Rasolan tradition as a reward or fringe benefit to their processors.